Exploring the Decision-making Process of Medical Students’ on Choosing Radiology as a Specialty in Northern Saudi Arabia: A Cross-sectional Study - Pakeeza Shafiq (Journal of Clinical and Diagnostic Research)
Introduction: Radiology is an important medical field that provides non invasive insights into the human body. However, the decision-making process regarding speciality choice among medical students is influenced by various personal, educational and societal factors. Aim: To identify the key factors that significantly shape the decision-making process of medical students. Materials and Methods: This cross-sectional study was conducted at the College of Medicine, Northern Border University, Arar, Kingdom of Saudi Arabia, from June to August 2024, involving 149 medical students, both males and females, in their clinical years (4th, 5th and 6th year). Data was collected using a predesigned proforma, along with demographic information. All data were entered into the Statistical Package for the Social Sciences (SPSS) Software version 22.0 for analysis. The normality of the data was checked using the Shapiro-Wilk test. Qualitative variables were presented as frequencies and percentages, while quantitative variables were presented as means with standard deviations. A p-value of ≤0.05 was considered statistically significant. Result: The gender distribution was 56 males (37.58%) and 93 females (62.42%), with only 16 participants (10.74%) having chosen radiology as their specialty, despite significant exposure to the specialty (76 participants, or 51.01%). Various factors, such as work-life balance, income, family expectations and patient contact, played a significant role in specialty choice. The Chi-square test found no significant association between gender and choice of specialty. Conclusion: Radiology’s critical role in patient diagnosis and management is well recognised, but factors such as academic performance, patient contact, family expectations and income significantly influence career choices among medical students. To attract more students to radiology, targeted educational initiatives and early exposure are essential.